A qualitative exploration of trust between general and special educators: Implications for collaboration in the preparation of teacher candidates - Meg Vostal; Brooks R. Vostal; Christy Galletta Horner; Kristina N. LaVenia (Social Sciences and Humanities Open, 2022)
Collaboration skills are addressed by educational organizations' teacher preparation standards. Collaboration is critical for effective service delivery to students with disabilities. Trust between educators is important for collaboration and effective shared service delivery. Investigations of collaboration between general and special educators are needed. We report findings from a qualitative investigation of trust and collaboration between general and special educators in one school district; participants taught elementary, middle, and high school. Results indicated that general and special educators struggled to build relational trust. Those who experienced trusting relationships promoted equity between roles and developed norms to support collaboration. Findings have implications for teacher preparation faculty who want to encourage positive collaborations.